1993
DOI: 10.1177/074193259301400103
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Paraprofessionals in Special Education

Abstract: In spite of a relative lack of evidence attesting to the efficacy of paraprofessionals in enhancing student outcomes, there has been a phenomenal growth in utilization of paraprofessionals in special education service delivery roles. A literature review indicated a need for additional information on this issue. Over the years the role of paraprofessionals has expanded to include increased use of these personnel for formal assessment, initial instruction, and home-school support, in addition to other activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 16 publications
2
44
0
2
Order By: Relevance
“…The literature is mostly descriptive in nature, and focuses on roles and responsibilities, as well as orientation and training. Only a few empirical studies, many outdated or lacking adequate controls, inquired about outcomes for students (Giangreco & Doyle, 2002;Giangreco, Edelman, & Broer, 2001a;Jones & Bender, 1993). Available findings show no clear empirical evidence to support claims of effectiveness of paraprofessional services to improve student achievement (Giangreco et al, 2001a;Gerber, Finn, Achilles, & Boyd-Zaharias, 2001).…”
Section: Evaluation and Effectiveness Of Paraprofessionalsmentioning
confidence: 94%
See 2 more Smart Citations
“…The literature is mostly descriptive in nature, and focuses on roles and responsibilities, as well as orientation and training. Only a few empirical studies, many outdated or lacking adequate controls, inquired about outcomes for students (Giangreco & Doyle, 2002;Giangreco, Edelman, & Broer, 2001a;Jones & Bender, 1993). Available findings show no clear empirical evidence to support claims of effectiveness of paraprofessional services to improve student achievement (Giangreco et al, 2001a;Gerber, Finn, Achilles, & Boyd-Zaharias, 2001).…”
Section: Evaluation and Effectiveness Of Paraprofessionalsmentioning
confidence: 94%
“…Nonetheless, the number of paraprofessionals in special and inclusion classrooms is rapidly increasing, and recent estimates suggest that over 600,000 paraprofessionals currently work in schools nationwide (Gerber et al, 2001). The appraisal of paraeducators' work by parents, students, teachers, administrators, and paraprofessionals themselves (Sullivan, 1998) is unequivocally supportive and favors the utilization of paraprofessionals especially for students with moderate to severe disabilities (Jones & Bender, 1993;Marks, Schrader, & Levine, 1999). This relative satisfaction with paraprofessionals may be related to teachers' perception of being supported in the classroom, and administrators' hopes for less staff turnover (Sullivan, 1998).…”
Section: Evaluation and Effectiveness Of Paraprofessionalsmentioning
confidence: 95%
See 1 more Smart Citation
“…The paraprofessionals have been found to have varying roles and responsibilities dependent on their experience and the dictates of the school in which they work. Many paraprofessionals have found that they are the front line workers with their students and the liaison between teacher and parent (Jones & Bender, 1993). They may sometimes advocate for the child, yet they frequently are left out of staff meetings or program planning team meetings.…”
Section: The Findings Of Other Researchersmentioning
confidence: 98%
“…• Les AE représentent le personnel auxiliaire le moins qualifié auprès d'élèves dont les difficultés d'adaptation sont les plus complexes (Carter, O'Rourke, Sisco et Pelsue, 2009;Chopra, Sandoval-Lucero, Aragon, Bernal, Berg De Balderas et Carroll, 2004;Jones et Bender, 1993;Katsiyannis, Hodge et Lanford, 2000). • Dans certains milieux scolaires, les méthodes d'intervention des AE tendent à faire plus de tort que de bien aux élèves concernés (Angelides, Constantinou et Leigh, 2009;Hardy, 2004;Riggs et Mueller, 2001;Rueda et Deneve, 1999).…”
Section: Tableau 2 Exemples De Responsabilités Ne Relevant Pas Des Funclassified